Tuning structure and mechanical properties of Ta-C coatings by N-alloying and vacancy population. Issue 1 (December 2018) - Glechner, T.; Mayrhofer, P.; Holec, D.; Fritze, S.; Lewin, E.; Paneta, V.; Primetzhofer, D.; Kolozsvári, S.; Riedl, H.
Abstract Tailoring mechanical properties of transition metal carbides by substituting carbon with nitrogen atoms is a highly interesting approach, as thereby the bonding state changes towards a more metallic like character and thus ductility can be increased. Based on ab initio calculations we could prove experimentally, that up to a nitrogen content of about 68% on the non-metallic sublattice, Ta-C-N crystals prevail a face centered cubic structure for sputter deposited thin films. The cubic structure is partly stabilized by non-metallic as well as Ta vacancies – the latter are decisive for nitrogen rich compositions. With increasing nitrogen content, the originally super-hard fcc-TaC0.71 thin films soften from 40 GPa to 26 GPa for TaC0.33 N0.67, accompanied by a decrease of the indentation modulus. With increasing nitrogen on the non-metallic sublattice (hence, decreasing C) the damage tolerance of Ta-C based coatings increases, when characterized after the Pugh and Pettifor criteria. Consequently, varying the non-metallic sublattice population allows for an effective tuning and designing of intrinsic coating properties.